Actividades Psicomotrices para fomentar la autonomía y el trabajo colaborativo en niños de 3 a 4 años - Tasinchana Chancusig, Lizbeth Geomayra (2023)
The limitations detected in the development of psychomotricity and autonomy in children from three to four years of age are due to several factors, including the use of didactic strategies such as collaborative work, from this the following objective is proposed to investigate: "Diagnose the Autonomy and psychomotricity through collaborative work in children from 3 to 4 years of age from the San José de Guaytacama Educational Unit in the 2023 school year. The research was directed under the qualitative, non-experimental approach, with a descriptive scope, the population was 25 children of the Initial 1 sub-level, and under the non-probabilistic sampling method, the decision was made to work with the twenty-five children. The investigative techniques to collect information were observation and the interview addressed to a teacher. The results of the investigation were the following: The teacher is unaware of didactic strategies to develop psychomotor skills and autonomy, as well as minimizes the contribution of collaborative work for the development of children's psychomotor and autonomous skills. In the observation, 22 indicators were raised under the following value scale: does not develop, in process, and develops, the results were: three children did not develop, fourteen children in the process, and eight children managed to develop the skills raised in the twenty-two indicators. It was concluded that there is a lack in the development of psychomotricity and autonomy under collaborative work because the results obtained were at the end of the school period, which implies that it is not developing adequately, according to the scientific literature, limiting the essential learning of children from three to four years in the cognitive area, affective psychomotor and social interaction.